Antibacterial activities of methanolic plant extracts - Zulhilmi Cheng, Mohamad Zulhafiz Shafiq (2015)
Methanolic extracts of twelve selected plants Premma cordiflora, Strobilanthes crispus, Cinnamomum iners, Annona squamosa, Barringtonia racermosa, Ipomoea aquatic, Gynura procumbers, Piper betle, Piper nigrum, Vigna unguiculata, Acalypha indica and Coleus amboinicus were tested against Escherichia coli, Klebsiella pneumoniae, Staphylococcus aureus and Bacillus cereus upon their antibacterial activities. Recently, some of the enstablish antibiotics have no longer effective to control bacterial diseases due to the occurrence of antibiotic resistance. In this project, all selected plants have shown to have an antibacterial activity toward selected bacteria except for V. unguiculata and A. indica. Extracts from C. iners showed high activity against E.coli and B.cereus. Throughout the project, 1% of DMSO been selected as negative control while erythromycin, penicillin-G and sulphamethoxazole been selected as the positive control. The minimum inhibitory concentration (MIC) for all the plant extracts been measure by using resazurin as the indicator based on Resazurin Microtiter Dilution Assay (RMDA). Extracts from C. iners, G. procumbers and B. racermosa have a MIC value at 1.56 mg/ml on E. coli, K. pneumoniae and S. aureus respectively while MIC value of C. iners, A. squamosa and B. racermosa for on B. cereus is 3.125 mg/ml.